DINAMIKA HUBUNGAN ANTAR AGAMA DAN MASYARAKAT - Martinus Duryadi (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2017)
This paper describes the dynamics of the relationship between religion and society in the minds of scientists. Charles Darwin saw religion as a system of symbols which continue to evolve from the simplest stage to forms more complex. The evolution of religion is an attempt to build a new understanding with regard to the context which is also new. Emile Durkheim viewed religion also has a social function is to maintain the unity of the community. Religion was able to build a collective consciousness to raise social solidarity. Max Weber also viewed religion capable of forming a particular social status. He looked specifically Protestantism strongly supports the creation of community capitalism. Only Karl Marx saw religion as pessimistic. He saw religion as the opium of the people. For him religion only gives false answers. Often religion conserving system-the system that oppresses.